Roles of Income Polarization, Income Inequality and Ethnic Fractionalization in Social Conflicts: An Empirical Study of Indonesian Provinces, 2002–2012. Issue 2 (21st August 2019) - Indra,; Nazara, Suahasil; Hartono, Djoni; Sumarto, Sudarno
Abstract : Previous studies have cited inequality as a major factor relating to conflicts in Indonesia, while consideration of polarization and fractionalization as drivers of conflict is limited. The current paper examined the roles of three indices (polarization, inequality and fractionalization) in explaining the incidence of conflicts in Indonesian provinces over 2002–2012. This study used income (proxied by expenditure) differences to measure polarization and inequality, with subnational data as the unit of analysis. In addition, to complete the analysis, the present study used a variety of socioeconomic indicators as additional control variables. This paper verified that the high degrees of income polarization, ethnic fractionalization and income inequality are associated with the high probability of conflicts in Indonesian provinces. It also found that socioeconomic factors such as poverty, unemployment, population and natural resources, as well as some types of local government spending are significantly associated with conflicts.